METHODOLOGICAL ASPECTS OF THE INTERCONNECTION IN THE DEVELOPMENT OF AVIATIONTRANSPORT SYSTEM AND AIRCRAFT INDUSTRY - Марінцева, К.В.; Юн, Г.М. (Science-based technologies, 2014)
It is considered a single two-level approach to the optimization of the main aircraft design parameters on early design stage. It is proposed bimodal procedure of external designing that is including operational and parametrical aircraft modeling.The proposed methodology brings some clarity in the organizational structure of design process and simulation, helps the developer of aircraft to systematize a large part of the known methods and algorithms for analysis and synthesis of complex technical systems; contributes to the quality of the project and reduce the time of design. Duplex procedure of external design effectively solves a number of new tasks that arise at the intersection of the optimal aircraftdesign and long-term planning of airline(potential customers of designed aircraft)economic activity.